Climate change impact under alternate realizations of climate scenarios on maize yield and biomass in Ghana. (January 2018) - Srivastava, Amit Kumar; Mboh, Cho Miltin; Zhao, Gang; Gaiser, Thomas; Ewert, Frank
Abstract: Climate change is unequivocal and these changes have increased over the past few years. The recent vulnerability and prospect of climate variability and change impact, thus, warrants measures now to reduce the adverse impacts. This study presents an estimate of the effects of climate variables on potential maize productivity and an assessment of the most limiting climatic drivers in the future climate scenarios for maize production in central Ghana, constituting major maize production areas. The time-slices 2000, 2030 and 2080 were chosen to represent the baseline, near future and end century climate, respectively. Furthermore, two Representative Concentration Pathways (RCPs ) namely RCP 4.5 and RCP 8.5 from the GFDL-ESM2M, GISS-E2-H, and HadGEM2-ES, General Circulation Models (GCMs), were selected. Simulations based on the model LINTUL5 were used to estimate the crop responses. There is an average increase in the maize yield and aboveground biomass in the projected scenarios by 57% and 59% respectively under HadGEM2-ES (RCP 8.5) in the time horizon 2030. However, variability in the projected average maize yield and above ground biomass compared to the baseline values, is ranging from 183.6 kg ha − 1 under HadGEM2-ES (RCP 8.5) by time horizon 2080 to a maximum of 1326.8 kg ha − 1 under HadGEM2-ES (RCP 8.5) by 2030 and a minimum increase of 169.9 kg ha − 1 under GFDL-ESM2M (RCP 8.5) by time horizon 2080 to a maximum increase of 2386.1 kg ha − 1 under HadGEM2-ES (RCP 8.5) by time horizon 2030. The reasons for potential benefit in maize yields across the climate scenarios was attributed to the positive effect of CO2, reduced water stress reflected by lower atmospheric water demand during crop growth period. It also indicates that water is the limiting factor for maize production in the study region. However, temperature (through shortening of the maize growing cycle), and solar radiation may remain the limiting factors for maize production. Highlights: The range of potential impact of climate change on maize productivity in Central Ghana was estimated. Yields gains were due to the beneficial effect of elevated CO2 on radiation use efficiency and reduced water stress. Temperature and solar radiation may remain the limiting factors for maize production under future climate conditions.